Design and application of enhanced communication protocols for wireless sensor networks operating in environmental monitoring. (5th July 2007) - Chiti, F.; Ciabatti, M.; Collodi, G.; Fantacci, Romano; , A. Manes
The effective application of Wireless Sensor Networks (WSNs) to wide area environmental monitoring currently represents a challenge for this technology. Since devices are usually energy constrained, smart power saving procedures are needed to increase the network lifetime. A common approach is to switch off the node's radio; this definitely requires the adoption of synchronisation procedures that properly schedule packets transmission to avoid both overhearing effects and collisions. To this end, a novel class of MAC layer protocols, named STAR MAC, is presented. This is further improved by introducing STAR+ scheme and properly integrating within a routing solution, according to the cross-layer design. It allows the optimisation of energetic consumption, or equivalently, network life-time, together with minimising the signalling overhead. The proposed solution is then applied to a realistic user-defined scenario, highlighting remarkable advantages both in terms of robustness, self reconfigurability, cost, complexity and QoS, thus validating the proposed solution.